Organized crime - Gandhirajan, C.K. (New Delhi, 2004)
Among the diversified forms of crime Organized Crime possess new threats and challenges to Law Enforcement Officials. In recent times it has assumed frightening propositions in all metropolitan cities.
Keywords: Crimes and criminology